Unraveling the genetic connections for mitochondrial DNA control region and breast cancer susceptibility - Namra Khalid; Muhammad Umer Khan; Raima Rehman; Shamsa Kanwal; Tazeen Zahid; Muhammad Usman Ghani; Ayesha Iftikhar; Qurban Ali; Muhammad Arshad Javed (Scientific Reports)
Abstract Breast cancer, a complex global health concern, has predominantly been studied for nuclear DNA variations. However, the role of mitochondrial DNA (mtDNA) haplogroups in breast cancer susceptibility, especially in Pakistan, remains underexplored. This case-control study investigates the association between mtDNA haplogroups and breast cancer in Pakistan. The study reveals a significant abundance of haplogroup M in breast cancer cases by analyzing breast cancer patients and healthy controls through mitochondrial control region genome sequencing (p < 0.001). Increased frequencies of haplogroups M, H, and R in patients compared to controls suggest their potential role in breast cancer susceptibility. Triple-Negative Breast Cancer (TNBC) cases are also linked to haplogroup M, showing a statistically significant association with a p-value of 0.002. This suggests a potential meaningful association between haplogroup M and the occurrence of TNBC in the studied population. These findings emphasize the importance of mitochondrial genetics in breast cancer risk among the Pakistani population, offering insights for biomarker discovery and targeted interventions. Recognizing mitochondrial genetics in breast cancer risk assessment holds promise for tailored medicine strategies and may impact global breast cancer research and prevention efforts.